Disparitas Putusan Mengenai Persamaan Pada Pokoknya Pada Merek Predator (Studi Putusan Nomor 1146 K/Pdt.Sus-Hki/2020) - Muhammad Ali Masnun (SASI, 2021)
The cases of trademark infringement on substantial similarity still relatively common in Indonesia. This article aims to analyze the basis for the judge's consideration in the decision Number 1146 K / Pdt.Sus-HKI / 2020. This is based on the disparity of Decision Number 69 / Pdt.Sus / Mark / 2019 / PN with Decision Number 1146 K / Pdt.Sus-HKI / 2020. This research uses doctrinal research using statute, case, and conceptual approaches. The results showed that the judges' basic considerations were not in accordance with regulations and several legal concepts. First, that the trademark protection system based on territorial territory and the first to file system principle should not be used as a basis for consideration. Second, that the two brands are basically similar because of the similarities in the dominant element and the similarity in sound or speech with the addition of the same class of goods. Third, the word "predator" cannot be categorized as a generic word, because the word predator has been added with a logo as a condition for a research, excluding generic brands. As a recommendation in deciding this matter, regarding the existence of bad faith, due to bad faith, a cancellation of a registered mark can be submitted indefinitely.